A Cultural Mechanism to Sustain Peace: How the Asabano Made and Ended War - Lohmann, Roger Ivar (Anthropologica, 2014)
Peaceful coexistence has replaced endemic warfare among the Asabano and other Om-Fu River peoples in Papua New Guinea. An Australian patrol making first contact in the 1960s curtailed warfare through threats. A decade later, Christian missionaries successfully communicated a ban on fighting and a mechanism for dispersing the vengeful feelings that had maintained payback cycles through prayer. Institutions forbidding raiding and a ritual engaging a supernatural agent who demands exclusive rights to revenge have defused local warfare for 50 years. This case suggests that peace can be indefinitely sustained through enculturating appropriate beliefs and scripts that are tailored for particular cultural contexts.